Byzantine Turns in Modern Greek Thought and Historiography, 1767-1874 - Kostantaras, Dean (The Historical Review/La Revue Historique, 2015)
This article examines representations of Byzantium in Modern Greek historical thought, from the first translation (1767) of the Corpus Scriptorum Historiae Byzantinae to the publication of Konstantinos Paparrigopoulos’ complete Ἱστορία τοῦ Ἑλληνικού Ἔθνους [History of the Greek nation (1860-1874)]. In doing so, it reassesses conventions, especially prevalent in English-language works, regarding the range and complexity of endeavors in this vein. Developments in European thought are used throughout as a vantage point, as they represent a contingency of great importance for any assessment of Greek attitudes toward the past. However, these influences did not always point in one direction; a factor which, in tandem with local generational and ideological divisions, helps to explain the diverse perspectives on Byzantium in Greek works from the period under review.